Perancangan Tata Letak Mesin Dengan Menggunakan Konsep Group Technology Sebagai Upaya Minimasi Jarak dan Biaya Material Handling - Kristinawati, Eti (Jurnal Teknik Industri, 2000)
PT. Berlina  Tbk Pandaan  is a company that  produce  already use plastic product  package. Some of its  product  are Nivea  bottle,  Lux shower  bottle,  packaging  of sheats  and the other  form variation. The processing to make it, need at least twice a process  of machine. All those  product through  some  operation  which  happened  a  long  way  material  handling  from  one  machine  to another.  As main product  facility  is through  the  the  machine  layout  can  be seen that  machine placement  still arbitrarily, and  it will  cause  product  current  longer so that  cost and  distance  fo rmaterial  handling also bigger.To solve this  problem,  we  have to  study  a theory  group  technology.  Major  point  f this theory  is  machine  grouping  become  machine  cell also  product  grouping  become  part family  so that,  later,  each machine cell will  produce a certain  of part family according  certain  criteria.  With the computer program called gtlaypc.exe, part family and machine cell can be know and use it for planning a machine layout.The result of machine  layout  planning  using  group technology  is  total  distance  27853,5  m per day and 18978  m per day smaller from the earlier  exiting  machine  layout  so  that the cost of material  handling  plan  Rp. 35109,3  per day more smaller.  Planning  the machine  layout  with the group technology  can minimalize of cost and distance material  handling